2013
DOI: 10.1074/jbc.m112.430900
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystal Structure of Escherichia coli RNA Polymerase σ70 Holoenzyme

Abstract: Background: A crystal structure of Escherichia coli RNA polymerase (RNAP) has not been determined. Results: The 1.1 and ␣ subunit C-terminal domain structures have been determined in the context of an intact RNAP. Conclusion: 1.1 localizes within the RNAP DNA-binding channel and must disengage from this site to form an open complex. Significance: This work enables future structure determination of bacterial RNAP mutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
224
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(241 citation statements)
references
References 61 publications
15
224
0
2
Order By: Relevance
“…The movement of the two domains toward each other by 5-10 Å and 10-15 Å, respectively, could easily bring β-SI1 close enough to interact with DksA. DksA binding could thus capture an alternative conformation to that found in the crystal structure of E. coli RNAP (23,(25)(26)(27)(28) and compete with any function of β-SI1 associated with this original conformation. Although we have clearly demonstrated that β-SI1 recruits DksA to RNAP, further efforts both to dissect this novel binding interface and to characterize the DksA-independent functions of β-SI1 will be critical for completing the picture of how the interaction between β-SI1 and DksA alters transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The movement of the two domains toward each other by 5-10 Å and 10-15 Å, respectively, could easily bring β-SI1 close enough to interact with DksA. DksA binding could thus capture an alternative conformation to that found in the crystal structure of E. coli RNAP (23,(25)(26)(27)(28) and compete with any function of β-SI1 associated with this original conformation. Although we have clearly demonstrated that β-SI1 recruits DksA to RNAP, further efforts both to dissect this novel binding interface and to characterize the DksA-independent functions of β-SI1 will be critical for completing the picture of how the interaction between β-SI1 and DksA alters transcription.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that DksA-D74 functions during initiation by neutralizing the positive charges of β-R678/ R1106 and altering the dense network of polar-electrostatic interactions in the immediate vicinity of the active center (23,26,28,29). This could alter the conformation of two neighboring mobile elements of β, fork loop-1 and fork loop-2, destabilizing the intermediate on the pathway to open complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the roles of the REC-DBD interface in transcription activation, we dock the E. coli RNAPH 18 to the PmrA-DNA complex structure on the basis of the crystal structure of the s 4 -b-flap tip helix chimer/PhoB-DBD/DNA ternary complex 29 (Supplementary Fig. 14).…”
Section: Discussionmentioning
confidence: 99%
“…The docking involved use of PyMOL 47 . The starting structures for docking were the PmrA-DNA complex structure (complex-1) and the E. coli RNAPH structure 18 (PDB-ID: 4IGC). The crystal structure of the s 4 -b-flap tip helix chimer/PhoB-DBD/DNA ternary complex 29 (PDB: 3T72) was used as a model to drive the structure-based alignment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation